Penyaluran Dana Bantuan Peningkatan Kesejahteraan Masyarakat Miskin di Kabupaten Tulungagung - Wijaya, Andy Fefta; -, Ismail (Jurnal Aplikasi Manajemen, 2009)
The Arrising of the world crude oil’s price has worsen the economic condition of Indonesia. The increasing charge of APBN because of subsidy’s, increasing, has forced the government to raise the price of domestic BBM. This policy causes the number of the poor of increases. So, the government conduct the program of BLT that is dedicated to the poor famielis in order to maintain the purchasing ability or to arise their prosperity But in the practice, the program of BLT is full of problem and influencing the poor. This research is conducted to understand the mechanism in distributing BLT in sub provience of Tulungagung, And abserve is social an economic effect toword poor people in Tulung agung. This research is descritive research by using cualitative approach, by using the method of taking note of the fact that is abserve in collecting data using the method of observation, interview, and also conducting documentation. This research shows that in distributing BLT in sub provience of Tulung agung, they are still wrong procedure, wrong target, insuffisien socialization, and the officers with lack of professionalism in doing their job (Responsible for distributing BLT). The result of this research shows that the distribution mechanism of the fun is not realized well we can find out the bad realization when we view it normative of view, it’s effisiensi and it’s effectivity, and if we observe it’s fairness toword the society. We can also find out that there is bad realization of the distribution of mechanism. It is shown by a lot of problem that happen in the distribution of BLT it self. A lot of officers that corrupt the fund, the schedule of distribution that often change, and the fund isn’t distriduted to the people who deserved to get it (Distribution that is wrong in the target).Keywords: fund (BLT), subsidy, distribution